Isotope analysis from IODP Core 339-U1389A-25X - Dorrik A V Stow; Zeinab Smillie; Jonathan Wilkin; Jiawei Pan; Onoriode Esegbue; André Bahr; Emmanuelle Ducassou (PANGAEA, 2024)
A further 48 samples were analysed for their organic carbon (TOC), CaCO~3~ and stable isotopic contents, using Elemental Analyser - Isotope Ratio Mass Spectrometry (EA-IRMS). These analyses were carried out at the Iso-Analytical labs, Wales. Nine samples received duplicate analysis, one sample was duplicated every 5 runs, indicating possible analytical error within <0.2%o for the δ13Ccarb and <0.15%o for both the δ13Corg and δ18O. Carbonate contents were extracted through acidification of the sample with 2M hydrochloric acid, drying and weighing the sample to calculate the weight loss. Total ion beam data was used to determine the carbon percent of the acid washed samples. The weight loss data recorded at the acid washing stage was used to calculate the TOC% values from the carbon percentages. The reference material used during δ 13Corg analysis were IA-R001 (δ13CV-PDB = -26.43 extperthousand), IA-R001, IA-R005 (δ13CV-PDB = -26.03 extperthousand) and IA-R006 (δ13CV-PDB = -11.64 extperthousand). Meanwhile, reference standards used for the carbonate isotopes were: IA-R022 (δ13CV-PDB = -28.63 extperthousand and δ18OV-PDB = -22.69 extperthousand), NBS-18 (δ13CV-PDB = -5.01 extperthousand and δ18OV-PDB = -23.20 extperthousand), IA-R066 (δ13CV-PDB = +2.33 extperthousand and δ18OV-PDB = -1.52 extperthousand), IAEA-603 (δ13CV-PDB = +2.46 extperthousand and δ18OV-PDB = -2.37 extperthousand) and IA-R040 (δ13CV-PDB = -0.72 extperthousand and δ18OV-PDB = -17.08 extperthousand).
In: Stow, DAV et al. (2024): Sediment and geochemistry of bi-gradational contourite sequences from the Gulf of Cadiz [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.937307